Adaptation behaviour of arable crop farmers towards drought in Kwara State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2026)
This study investigates the adaptation behaviour of arable crop farmers in Kwara State, Nigeria. A multistage sampling procedure was used in selecting 200 respondents for the study. Data were obtained using an interview schedule and were analysed using percentages, means, standard deviation, and multiple regression at p≤0.05. The results showed that ridging (x̄ = 1.78), planting cover crops to prevent erosion and retain moisture (x̄ = 1.39), and use of legumes to improve soil fertility naturally (x̄ = 1.12) were the most frequent drought management practices used by the arable farmers. The overall adaptation behaviour towards drought was poor (x̄ = 2.84). Age (β = -0.118), household size (β = 0.278), access to weather forecast information (β = 0.319), land ownership status (β = 0.507), and access to irrigation facilities (β = 0.109) significantly influenced the adaptation behaviour of the respondent towards drought. The study recommended increased investment on localized weather forecasting systems and targeted training programs on climate-smart agriculture and drought mitigation techniques.
Keywords: Agricultural production; Climate-smart farming; Food security; Vulnerability